(untitled) (ENTHYMEMA, 2013)
The article reconstructs the genesis of the work by Gianni Carchi, Dall’Apparenza al Mistero. La nascita del romanzo. The aim is twofold: on the one hand a more general interest in Carchia’s ideas on the birth of the novel, and on the other to reconsider some of the notions presented in the book, which reframe the issue of the novel in philosophical perspective.